Prevalence of Juvenile Fibromyalgia Syndrome Among Children and Adolescents and its Relationship With Academic Success, Depression and Quality of Life, Çorum Province, Turkey - Ayla ÇAGLIYAN TÜRK; Füsun ŞAHİN (Archives of Rheumatology, 2020)
Objectives: This study aims to determine the frequency of juvenile fibromyalgia syndrome (JFMS) among children and adolescents in Çorum Province, Turkey, and its impact by comparing the levels of academic success, depression and quality of life (QoL) in individuals with and without JFMS. Patients and methods: This was a cross-sectional study on 476 children and adolescents (245 boys, 231 girls; mean age 13.81±2.3 years; range, 9 to 17 years). The control group (non-JFMS group) consisted of 105 age- and sex-matched healthy participants (75 girls, 30 boys; mean age 14.1±1.8 years; range; 9 to 17 years). Participants’ sociodemographic data, parental information, and school achievement in addition to data on chronic illness and drug use were collected via questionnaires (depression and QoL). A tender point (TP) examination was performed on each participant. Results: Thirty-five (7.35%) of the participants (girls, n=25; boys, n=10) were diagnosed with JFMS. The number of minor JFMS diagnostic criteria, number of TPs, depression level and number of days the participants were absent from school were significantly higher in the JFMS group compared with the non-JFMS group (p<0.05). The mean grade point scores of the JFMS group were significantly lower than those of the non-JFMS group (p<0.05). The QoL subgroup scores as assessed by physical functioning, emotional functioning, social functioning and school-related problems of the JFMS group were significantly lower than the non-JFMS group (p<0.05). Age had a statistically significant negative correlation with QoL and school-related problems (r= -0.421, r= -0.494; p<0.05, respectively). Depression was negatively correlated with QoL and school-related problems (r= -0.672, r= -0.731; p<0.05, respectively). Conclusion: Juvenile fibromyalgia syndrome affects QoL and can lead to school absenteeism, poor academic performance, depression and anxiety among the school-age population. Early identification of JFMS and early intervention may be the most effective strategy for preventing problems in later life.